2012
DOI: 10.1590/s0102-86502012001000003
|View full text |Cite
|
Sign up to set email alerts
|

An experimental model for the study of collagen fibers in skeletal muscle

Abstract: This methodology is important for the identification and quantification of the different types of collagen in muscles and can be used in the investigation of the qualitative and quantitative influence of collagen on physical activities, aging, and diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 15 publications
(14 reference statements)
2
25
1
5
Order By: Relevance
“…However type III collagen was reduced after seven days compared to the control group, and then increased up to 14 days after injury (de Souza et al). As the present study did not differentiate between types of collagen, the collagen could have been reduced in the L7 group due to the reduction of type III collagen, which was not compensated for by the increase of collagen type I. Collagen is an important component of skeletal muscle, it is responsible for structure, organizing the muscle tissue at various levels, from the fascia and epimysium to the perimysium and endomysium, being mainly composed of collagen type I and III (Calvi et al, 2012) This study aimed to demonstrate a new technique for analyzing muscle injury in histological slides; however, some limitations should be noted: the injury protocol, despite having the advantage of not being invasive, allowed for a small variation in the extent of injury, due to differences between animals, such as the length of the hind limb; fractal analysis of collagen using the picrosirius method is not able to differentiate between the types of collagens by showing different colors on histological slides, because after the binarization process all the different colors of collagen had become black.…”
Section: Discussioncontrasting
confidence: 56%
“…However type III collagen was reduced after seven days compared to the control group, and then increased up to 14 days after injury (de Souza et al). As the present study did not differentiate between types of collagen, the collagen could have been reduced in the L7 group due to the reduction of type III collagen, which was not compensated for by the increase of collagen type I. Collagen is an important component of skeletal muscle, it is responsible for structure, organizing the muscle tissue at various levels, from the fascia and epimysium to the perimysium and endomysium, being mainly composed of collagen type I and III (Calvi et al, 2012) This study aimed to demonstrate a new technique for analyzing muscle injury in histological slides; however, some limitations should be noted: the injury protocol, despite having the advantage of not being invasive, allowed for a small variation in the extent of injury, due to differences between animals, such as the length of the hind limb; fractal analysis of collagen using the picrosirius method is not able to differentiate between the types of collagens by showing different colors on histological slides, because after the binarization process all the different colors of collagen had become black.…”
Section: Discussioncontrasting
confidence: 56%
“…Moreover, these mesenchymal cells eventually form the continuous bands of the future orbicularis oris muscle (Lazzeri et al, ), which is shown to have altered diameter (Khan et al, ; Khan, Little, Abelli, Mossey, et al, ; Khan, Little, Mossey, Steegers‐Theunissen, Bonsi, et al, ) and arrangement (Wijayaweera, Amaratunga, & Angunawela, ) across the two sides in CL cases. Notably, collagen and muscles share structural–functional relationship to ensure proper alignment (Calvi et al, ). Therefore, observation of changes in the orbicularis oris muscles across the two sides could be an outcome of changes in distribution of CF‐ED, which affects the medial side more than the lateral side in cases with CL.…”
Section: Discussionmentioning
confidence: 99%
“…Specimen longitudinal sections of 5-10 mm in thickness were stained with hematoxylin and eosin (H&E) (Sigma-Aldrich) to visualize nuclei, or stained with Alcian blue (SigmaAldrich) for GAG deposition, 34,35 or stained with Masson's trichrome (Sigma-Aldrich) to observe total collagen. 36,37 Type II collagen was immunolocalized by an anti-type II collagen antibody (bs-0709r; Bioss) with a 1:100 dilution in Tris-buffered saline with Tween 20 solution, and the signal was amplified with an UltraVision Quanto Detection System (Thermo Scientific) for 10 min, followed by diaminobenzidine for visualization as described by the manufacturer. Nuclei were counterstained with hematoxylin.…”
Section: Characterizations Of Acellular Ecm Scaffoldsmentioning
confidence: 99%